2012
DOI: 10.1364/boe.3.000225
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive optics with pupil tracking for high resolution retinal imaging

Abstract: Adaptive optics, when integrated into retinal imaging systems, compensates for rapidly changing ocular aberrations in real time and results in improved high resolution images that reveal the photoreceptor mosaic. Imaging the retina at high resolution has numerous potential medical applications, and yet for the development of commercial products that can be used in the clinic, the complexity and high cost of the present research systems have to be addressed. We present a new method to control the deformable mir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 19 publications
(25 reference statements)
1
20
0
Order By: Relevance
“…Comparing what is expected from a pupil tracking at 10 Hz (which corresponds to an ideal AO set-up at 10 Hz with perfect WFS measurement and DM correction) with a pupil tracking at 80 Hz, the performance improvement in terms of wavefront rms is significant. We have compared the error budget caused by the pupil displacement with real experiments presented in [16], for a system running at around 10 Hz. It is shown that for such a system, the maximum degradation impact due to pupil displacement when compared with the use of a PT at 80 Hz may be significant.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Comparing what is expected from a pupil tracking at 10 Hz (which corresponds to an ideal AO set-up at 10 Hz with perfect WFS measurement and DM correction) with a pupil tracking at 80 Hz, the performance improvement in terms of wavefront rms is significant. We have compared the error budget caused by the pupil displacement with real experiments presented in [16], for a system running at around 10 Hz. It is shown that for such a system, the maximum degradation impact due to pupil displacement when compared with the use of a PT at 80 Hz may be significant.…”
Section: Discussionmentioning
confidence: 99%
“…The advantage of a PT as the one analyzed here is that it can run at a faster rate than the wavefront sensor, as mentioned in [16]. Any analysis of error budget here requires therefore the computation of differences between a reference phase screen (the corrected one) and a displaced phase screen.…”
Section: Wavefront Error Analysismentioning
confidence: 99%
See 3 more Smart Citations